Actors' Cooperation in Overcoming Street Children: Kerjasama Aktor dalam Mengatasi Masalah Anak Jalanan - Masfufah, Dwi Nur; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative field research aimed to determine the synergy of actors in handling street children in Sidoarjo District, Indonesia. The study found that the implementation process of the policy for handling street children involved various stakeholders, both government and non-government, and was incorporated in a special coordination team called the Street Children Outreach Team. The team had a clear division of roles, and the stakeholders negotiated to avoid domination of one another's roles. The indicators and objectives that must be met by stakeholders in working together include the 4R approach, namely rights, responsibilities, revenues, and relationships. The study implies that effective collaboration among stakeholders is crucial in handling street children, and a clear division of roles can prevent conflicts and ensure the success of the program. Highlight : The study emphasizes the importance of a clear division of roles among stakeholders in handling street children. The Street Children Outreach Team in Sidoarjo District involves various government and non-government stakeholders, working together with a 4R approach (rights, responsibilities, revenues, and relationships). Effective collaboration among stakeholders is crucial in handling street children, and it can be achieved through the negotiation to avoid the domination of one another's roles. Keywords: Synergy of actors, Street children, Stakeholders, Sidoarjo District, Indonesia